Shake Table Tests on One-Quarter Scale Models of Masonry Houses Retrofitted with PP-Band Mesh - Sathiparan, N.; Mayorca, M.; Meguro, K. (My University, 2012)
This paper introduces a technically feasible and economically affordable retrofitting option for seismically vulnerable masonry structures in developing countries using polypropylene bands (PP-bands). The results of the basic material tests and shake table tests on building models show that the PP-band retrofitting technique can enhance the safety of both existing and new masonry buildings, even during severe ground motions, for instance an earthquake with a Japan Meteorological Agency (JMA) seismic intensity of 7. Therefore, the proposed method is an optimum solution for promoting safer building construction in developing countries and can contribute to earthquake disaster mitigation in the future. [DOI: 10.1193/1.3675357